Implementasi Active Learning Strategy untuk Meningkatkan Prestasi Siswa pada Mata Pelajaran IPS di SMP Islam Al-Waroqot Pamekasan - Vera Indriana; Itaanis Tianah; Ahmad Imam Khairi; Shinta Oktafiana (ENTITA: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2022)
The active learning strategy is using for increase student’s liveliness. This research is a Classroom Action Research (CAR) using the action research model of Kemmis and MC Taggart, which is in the form of a spiral from one cycle to another. Each cycle includes planning, action, observation, and reflection. The results of this study indicate that social studies learning in the material of Interaction between ASEAN countries by implementing active learning strategies with the active knowledge sharing method in Class 8 of Al-Waroqot Islamic Junior High School has a positive impact in improving student learning outcomes. This can be seen from the results of student tests that have reached. The average score of students' test classically reached 88 from the previous 72.83 with 83.3% learning completeness. After the remedy was held, the average score of the students' test classically was 88 with 100% learning completeness. Keywords: active learning strategies, IPS learning outcomes.